I'll marry you if you get me a job: marital assimilation and immigrant employment rates - Delia Furtado; Nikolaos Theodoropoulos (Institute for the Study of Labor (IZA), 2009)
Marriage to a native has a theoretically ambiguous impact on immigrant employment rates. Utilizing 2000 U.S. Census data, this paper empirically tests whether and how marriage choice affects the probability that an immigrant is employed. Results from an ordinary least squares model controlling for the usual measures of human capital and immigrant assimilation suggest that marriage to a native increases an immigrant's employment probability by approximately four percentage points. The estimated impact of marriage to a native increases to 11 percentage points in models which take into account the endogeneity of the intermarriage decision.
urn:nbn:de:101:1-20090209213
Keywords: J12; J61; 330; Intermarriage; employment; immigration; Migranten; Berufliche Integration; Ehe; Soziale Integration; Ethnische Beziehungen; USA